An analysis of levels and factors of teacher-librarian collaboration in selected public science high schools in Metro Manila - Trinidad, Jerome V.; Gonzales, Grace Marie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2013)
School libraries exist to support the education the school brings. In the 21st century, our school librarians are changing roles in order to add more in this support. In all their new roles as information specialist, teacher, instructional partner and program administrator (AASL & AECT, 1998), they have to involve themselves in a healthy collaboration with teachers.
This study was undertaken to find out the present level of collaboration among the selected schools (Makati Science, Muntinlupa Science, Philippine Science (Main) and Valenzuela City Science High Schools) and determine the factors that correlate to a higher collaboration. The levels of collaboration in this study follow the taxonomies of Loertscher (2000).
The factors that were considered in this study were on school environment, teachers' and librarians' interpersonal characteristics, process and structure, communication, shared purpose, and resources. Under the school environment, number of colleagues doing the collaboration, expectation from the Principal and occurrence of meetings with both parties; under the interpersonal characteristics, trust level of teachers and librarians toward each other; under the process and structure, status of librarians and tasks conducted by librarians; under the communication, frequency of work, and non-work related conversations; under shared purpose, perceived beneficiaries of teacher-librarian collaboration and perceived purpose of the collaboration; and under the resources, time, budget and library collection.
This correlation study used two sets of questionnaires - one for the teachers and another for the librarians-and semi-structured interview for the (head) librarians. Questionnaires were sent out to 4 schools and returned 57 responses from the teachers and 7 from the librarians. Responses were analyzed with Spearman-rank coefficient of correlation and were tested for significance of association with a level of significance of 0.10.
The results of the study revealed that majority of teachers are at the lowest level of teacher-librarian collaboration while majority of librarians are at a high level of 7 or 9 of TLC. General findings concluded that levels of TLC has a significant relationship with the following factors: under the school environment, numbers of teachers seeking help from librarians and expectation from the Principal; under interpersonal characteristics, trust level; under process and structure, perception of tasks of librarians; under communication, work-related conversations; under shared purpose, perception on who benefits from TLC and purpose of the collaboration; under resources, availability to visit the library and quality of library collection. Each school, however and also, has their own different accounts of the study.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Libraries and education -- Philippines -- Manila Metropolitan Area; High school librarians -- Philippines -- Manila Metropolitan Area; High school teachers -- Philippines -- Manila Metropolitan Area